Functional properties of nata biocellulose from coconut milk medium - Fadrilan, Lloyd Myla S.
ABSTRACT Nata biocellulose was developed from class A nata de coco fermented from coconut milk medium. Freeze drying was selected as the dehydration method because it produced nata biocellulose of higher yield and quality. these production runs yielded a mean of 0.442% recovery with a moisture content ranging from 1.337% to 1.598%. the freeze dried nata was characterized as Zinc white / snowy white in color with a fibrous texture. Its functional properties were investigated and compared with powdered microcrystalline cellulose (MCC) of plant origin as the standard reference. The means of the water binding capacities (WBC), corn oil retention capacities (CORC) and emulsifying activities, 19.703, 19.666 and 77.778% respectively, of nata boicellulose were significantly higher (P ≤0.05, P ≤0.0002) than those of MCC, 3.5122, 3.3376, and 8.3333% respectively. Minimum dispersibilities were observed between pH 3 and 7 at concentrations ranging from .5% to 2% for nata biocellulose. MCC was dispersible in water at all concentrations (.5%, 1% 2%), pH (3, 5, 7) and temperature (room temp.,60°, 80°, 100 used. n both cases of nata biocellulose and MCC, maximum dispersibility was noted at 100°C. However, no trend was derived to generalize the effect of concentration, pH and temperature on nata biocellulose and MCC. The two cellulose displayed different dispersibility profile in varying concentration, pH and temperature. Electron microscope observation revealed a dense network of long fibers with a average thickness of 50 nm (500 A) and an undeterminable length. Close parallel packing of nata fiber consisting of intertwining microfibrils was also discernibl